2015
DOI: 10.4251/wjgo.v7.i11.361
|View full text |Cite
|
Sign up to set email alerts
|

Tumor neoangiogenesis detection by confocal laser endomicroscopy and anti-CD105 antibody: Pilot study

Abstract: AIM:To evaluate neoangiogenesis in patients with colon cancer by two fluorescently labeled antibodies on fresh biopsy samples imaged with confocal laser endomicroscopy (CLE). . When using the anti-CD31 antibody, the average diameter of vessels in the normal colon tissue was 7.67 ± 0.5 μm and the vessel density was 3191.60 ± 387.8 vessels/mm 3 , while in the tumors we obtained an average diameter of 10.88 ± 0.8 μm and a vessel density of 4707.30 ± 448.85 vessels/mm 3 . Thus, there were more vessels stained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…The present investigation is the first to take into account the analysis of tumor vasculature by pCLE in a considerable number of rectal and gastric cancers. Two recent studies showed that the use of confocal laser endomicroscopy in colorectal cancers was suitable for measuring more vascular parameters than conventional immunohistochemistry alone, and for detecting tumor neoangiogenesis with fluorescently labeled antibodies 31 , 32 . The approach used by the authors was completely different: the pCLE analysis was not performed during the endoscopic examination but on fresh tumor biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation is the first to take into account the analysis of tumor vasculature by pCLE in a considerable number of rectal and gastric cancers. Two recent studies showed that the use of confocal laser endomicroscopy in colorectal cancers was suitable for measuring more vascular parameters than conventional immunohistochemistry alone, and for detecting tumor neoangiogenesis with fluorescently labeled antibodies 31 , 32 . The approach used by the authors was completely different: the pCLE analysis was not performed during the endoscopic examination but on fresh tumor biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Endoglin, tümör içinde veya çevresinde yüksek hassasiyete sahip küçük damarları boyarken, neoplastik olmayan dokudaki kan damarlarını boyamadığı veya sadece zayıf boyadığı ifade edilmiştir. Buna karşılık CD31'in ise tüm kan damarlarını ayrım gözetmeden boyadığı görülmüştür [25,26]. Glioblastomlu hastalar üzerinde yapılan çalışmada da benzer sonuca ulaşılmış, endoglinin glioblastomadaki anjiyogenezin değerlendirilmesinde CD31'e göre daha spesifik ve hassas bir belirteç olduğu gösterilmiştir [27].…”
Section: Discussionunclassified
“…The most used dye is fluorescein which has a safety profile, and has the ability of highlighting the vessels. However, the direction seems to be toward individualized situations whereas specific antibodies such as CD 31, CD105, and EGFR [24,25] might be more useful for tissue architecture description. CLE is considered a valuable tool with great potential that may overcome some of the disadvantages of classic histology such as time waiting or sampling bias, thus facilitating live diagnosis and treatment decisions.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%